Artificial Intelligence in Morocco: Current Situation and Recommendations - BENABBOU, Zineb; NAFZAOUI, Mohamed Achraf (Revue Internationale du Chercheur, 2024)
The article examines the progress and challenges of artificial intelligence (AI) in Morocco. The country has made significant advancements in the digital realm through investments in telecommunications infrastructure and programs like "Maroc Digital 2020." AI is being applied in various domains such as license plate recognition, traffic management, and satellite imagery for agriculture. AI technologies are also being used to optimize public transportation and for facial recognition in airports, thereby contributing to the security and efficiency of public services. However, ethical issues and concerns regarding privacy protection persist, particularly regarding the transparency and accountability of AI systems. In this article, adopting an analytical approach, we assess the current state of AI in Morocco by surveying the evolution of digitalization, then examining Morocco's positioning in the global AI landscape, subsequently highlighting pioneering AI projects and sectors in Morocco, and concluding with the challenges that remain following the advent of this technology. We conclude with recommendations for overcoming these challenges to ensure a responsible and beneficial adoption for society.